P08.01 Low-dose checkpoint inhibitors with hyperthermia and IL-2 are safe and effective in stage IV cancer with unfavorable immunological profile (MSIlow, PD-L1 under 1%, TMBlow) – A single-institution experience from 2015 to 2020. (1st October 2020) - Kleef, R; Nagy, R; Bacher, V; Bakacs, T; Lausch, T; McKee, D; Moss, R; Bojar, H; Thoennissen, N
Abstract : Background: Close to 10 million cancer deaths occurred worldwide in 2017 primarily due to stage IV disease, the management of which is still palliative by intent. Differently from melanoma and non-small cell lung cancer, where the use of ground-breaking immune checkpoint inhibitors (ICI) results in a relatively high efficacy, the response rate in many other stage IV tumors, such as gastrointestinal cancers, breast cancers, sarcomas, and part of genitourinary cancers remains low. In addition, administration of this type of cancer immunotherapy is known for its potentially severe and even fatal side effects due to their severe immune-related adverse events (irAEs). Materials and Methods: Here, we report a retrospective analysis of 129 patients with stage IV cancer who exhausted conventional treatments, who were treated by an low-dose ipilimumab (0.3 mg/kg) plus nivolumab (0.5 mg/kg) blockade in combination with individually dose adapted interleukin 2 (IL-2) treatment under taurolidine protection and locoregional- and whole body hyperthermia. Results: The overall response (OR) rate of the 129 stage IV patients was 49.6% with an objective response (ORR) of 31.8%. In 15 stage I-III cancer patients, the overall response (OR) rate and objective response (ORR) were 93%, respectively. The entire treatment was performed as outpatient therapy which was mostly associated with a toxicity of grade 1–2 (24.4 and 14.9%, respectively), including nausea, diarrhea, skin rash and pruritus, and elevation of liver transaminases during the first 24 hours. Only 4, 76% of the patients developed grade III and 1, 79% grade IV irAEs, such as autoimmune hepatitis, thyroid problems, acute kidney injury and/or diabetes mellitus. There were no signs of late adverse events from this treatment with follow-up greater than 5 years post therapy. Conclusions: In comparison to the commonly known rates of response and side effects in ICI, we were able to show relatively high response rates in parallel with low toxicity profile by the aid of immune response modifiers. Disclosure Information: R. Kleef: None. R. Nagy: None. V. Bacher: None. T. Bakacs: None. T. Lausch: None. D. McKee: None. R. Moss: None. H. Bojar: None. N. Thoennissen: None.